Evaluation of Methanolic Extract of Hypericum Mysorense Ointment for its Wound Healing Activity (Global Journal of Medical Research, 2020)
The main objective of the present study is to formulate and evaluate semi-solid dosage forms of Hypericum mysorense for its wound healing activity. The stem of Hypericummysorense was extracted by continuous hot percolation/ soxhletationusing methanol as solvent and was evaluated for its phytochemical property, in-vitro antimicrobial andin-vitro antioxidant activity. Using this methanolic extract, semi-solid dosage form(ointment) was formulated. Ointment was prepared using 2% concentration of the extract by fusion method using emulsifying ointment. Hence, the ointment containing 2% methanolic extract of Hypericummy-sorense was evaluated for its wound healing activity using excision wound model. The effect produced by the extract ointment, in terms of wound contracting ability, wound closure time and histopathological characteristics were comparable to that of a standard drug povidone iodine ointment. Therefore, the present study concluded that the Hypericum mysorense at 2% concentration of the methanolic extract formulated as an ointment showed a better wound healing formulation for better patient care and pharmaco economical.
Keywords: hypericum mysorense; excision wound model; ointment